2006
DOI: 10.1200/jco.2006.24.18_suppl.2038
|View full text |Cite
|
Sign up to set email alerts
|

A phase I repeated dose escalation study of the Polo-like kinase 1 inhibitor BI 2536 in patients with advanced solid tumours

Abstract: 2038 Background: BI 2536 is a novel highly potent and selective inhibitor of the serine-threonine kinase polo-like kinase 1 (Plk1), which is a key regulator of cell cycle progression. Objectives of this trial were the assessment of the maximum tolerated dose (MTD), overall safety, pharmacokinetics and efficacy of BI 2536 given intravenously. Methods: Sequential cohorts of 3 to 6 patients (pts) with pretreated advanced or metastatic solid tumours received intravenous infusions of BI 2536 on days 1 and 8 of a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Data from the first in-man studies investigating the safety and pharmacokinetics (PKs) of BI 2536 in patients with advanced tumors demonstrated that BI 2536 was well tolerated, had a favorable PK profile, and showed potential antitumor activity. [12][13][14] When BI 2536 was administered as a single intravenous (iv) infusion or a daily infusion for 3 days, the maximum tolerated doses were 200 and 60 mg/d for the single iv infusion and the 3-consecutive-day infusion, respectively. 14 The most frequently observed adverse events (AEs) consisted of nausea, anorexia, fatigue, vomiting, and mucositis and were mostly of mild to moderate intensity.…”
mentioning
confidence: 99%
“…Data from the first in-man studies investigating the safety and pharmacokinetics (PKs) of BI 2536 in patients with advanced tumors demonstrated that BI 2536 was well tolerated, had a favorable PK profile, and showed potential antitumor activity. [12][13][14] When BI 2536 was administered as a single intravenous (iv) infusion or a daily infusion for 3 days, the maximum tolerated doses were 200 and 60 mg/d for the single iv infusion and the 3-consecutive-day infusion, respectively. 14 The most frequently observed adverse events (AEs) consisted of nausea, anorexia, fatigue, vomiting, and mucositis and were mostly of mild to moderate intensity.…”
mentioning
confidence: 99%